Representation of Memory and Historical Trauma in the Film The Time That Remains - Ar Zaki, Achmad Miftachul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Film often serves as a medium that represents the history and collective memory of a society. This study aims to analyze the representation of historical memory and trauma in The Time That Remains, a film directed by Elia Suleiman. The film portrays the life of a Palestinian family across several time periods related to the political conflict from 1948 to the contemporary era. Through family narratives and various scenes of everyday life, the film presents representations of historical experiences that shape both individual and collective identities within Palestinian society. This research employs a qualitative approach using a film analysis method that focuses on narrative and visual elements. The analysis is conducted by examining several key scenes in the film related to experiences of conflict, family life, and the representation of the main characters. The theoretical framework of this study draws on the perspective of cultural memory, which views film as a medium for representing the collective memory of society formed through historical experiences and political conflict. The results of the study indicate that the film represents the collective memory of Palestinian society through family narratives, a fragmented narrative structure, and the use of a minimalist visual style. Historical trauma is not only depicted through scenes of conflict but also through the silence of characters, social spaces, and everyday activities that reflect the experiences of people living under the shadow of conflict. Thus, the film can be understood as a cinematic representation of cultural memory that records the historical experiences of Palestinian society.